Various Green Nanomaterials Used for Wastewater and Soil Treatment: A Mini-Review - Nakum, Jayraj; Bhattacharya, Debleena (Frontiers in Environmental Science, 2022)
The industrial intervention had a profound impact on our environment and the amount of damage it has bestowed is in the form of polluted water and solid waste accumulation. With upgradation of technologies in the industrial upfront there is also an increase in the robust nature of industrial waste. Keeping in view the various environmental aspects, advanced techniques were developed by the inculcation of nanotechnology. Among the diverse technologies that have gained prominence is the use of nanoparticles as a medium to monitor the treatment process. One of them is the use of organic techniques i.e. vermi-sand filters for purifying the wastewater. The review article focuses on the new data pertaining to the study and improvement of various nano-scale treatment technologies implemented for wastewater treatment with an environment friendly biodegradation. The whole concept can be made friendlier to the environment and economy by the use of renewable energy (e.g. Solar) for electrical supply to the wastewater treatment plant for its management.